Galaxy and MEAN Stack to Create a User-Friendly Workflow for the Rational Optimization of Cancer Chemotherapy - Pires, Jorge Guerra; da Silva, Gilberto Ferreira; Weyssow, Thomas; Conforte, Alessandra Jordano; Pagnoncelli, Dante; da Silva, Fabricio Alves Barbosa; Carels, Nicolas (Frontiers in Genetics, 2021)
One aspect of personalized medicine is aiming at identifying specific targets for therapy considering the gene expression profile of each patient individually. The real-world implementation of this approach is better achieved by user-friendly bioinformatics systems for healthcare professionals. In this report, we present an online platform that endows users with an interface designed using MEAN stack supported by a Galaxy pipeline. This pipeline targets connection hubs in the subnetworks formed by the interactions between the proteins of genes that are up-regulated in tumors. This strategy has been proved to be suitable for the inhibition of tumor growth and metastasis in vitro. Therefore, Perl and Python scripts were enclosed in Galaxy for translating RNA-seq data into protein targets suitable for the chemotherapy of solid tumors. Consequently, we validated the process of target diagnosis by (i) reference to sub-network entropy, (ii) the critical value of density probability of differential gene expression, and (iii) the inhibition of the most relevant targets according to TCGA and GDC data. Finally, in future releases of the application, the most relevant targets identified by the pipeline shall be stored using MongoDB and shall be accessed through the aforementioned internet portal designed to be compatible with mobile or small devices through Angular libraries.